Absence of Standard Modifiable Risk Factors in Middle Eastern Patients with Atherosclerotic Cardiovascular Disease. The Jordan Absence of Standard Modifiable Risk Factors (SMuRF-Less) Study - Hammoudeh AJ; Aldalal’ah M; Smadi EA; Alrishoud D; Alomari A; Alkhawaldeh M; Rizik A; Okour MF; Araydah M (Vascular Health and Risk Management)
Ayman J Hammoudeh,1 Mo’men Aldalal’ah,2 Elham A Smadi,2 Dima Alrishoud,2 Amal Alomari,2 Mahmoud Alkhawaldeh,3 Aseel Rizik,4 Mahmoud Fakhri Okour,5 Mohammad Araydah6 1Department of Cardiology, Istishari Hospital, Amman, Jordan; 2Department of Clinical Medical Sciences, Yarmouk University School of Medicine, Irbid, Jordan; 3Department of Internal Medicine, King Abdullah University Hospital, Irbid, Jordan; 4Department of Medical Education, University of Jordan School of Medicine, Amman, Jordan; 5Department of Internal Medicine, Tutanji General Hospital, Amman, Jordan; 6Department of Internal Medicine, Istishari Hospital, Amman, JordanCorrespondence: Ayman J Hammoudeh, Department of Cardiology, Istishari Hospital, 44 Kindi Street, Amman, 11954, Jordan, Tel + 9626 500 1000, Fax + 9626 693 8833, Email a.hammoudeh@istisharihospital.comBackground: A growing number of individuals develop atherosclerotic cardiovascular disease (ASCVD) despite the absence of the standard modifiable risk factors (hypertension, diabetes, dyslipidemia, and cigarette smoking) (SMuRF-less patients). Prevalence of SMuRF-less patients in the Middle East has not been studied. This study investigates the prevalence, clinical profiles and outcomes of SMuRF-less patients compared with those who have SMuRFs.Methods: We analyzed data from 6 published registries and from the Jordan SMuRF-less patients study, including baseline demographic features, cardiovascular risk factors, comorbid diseases, utilization of secondary prevention pharmacotherapy and one year outcome in SMuRF-less patients, those with 1– 2 SMuRFs and with 3– 4 SMuRFs. Results. A total of f 5540 ASCVD patients were enrolled. Mean age was 57.5 ± 11.6 years, and 1333 (24.1%) were women. Of the whole group, 214 (3.9%) were SMuRF-less, 3014 (54.4%) had 1– 2 SMuRFs and 2312 (41.7%) had 3– 4 SMuRFs. Compared with the SMuRFs groups, SMuRF-less group were younger, more likely to be men, and had lower prevalence of obesity, physical inactivity, metabolic syndrome, heart failure and chronic kidney disease. SMuRF-less patients were less likely to receive secondary prevention cardiovascular medications (antiplatelet agents, statins, renin angiotensin blockers and beta blockers); all p < 0.001. One year survival in the SMuRF-less patients was significantly lower than that in the SMuRFs groups (97.7% vs.98.4% vs.98.3%, respectively, p = 0.01). Multivariate analysis showed that young age, absence of heart failure and utilization of secondary preventive medications were associated with better one year outcome.Conclusion: In this cohort of ME patients with ASCVD, nearly four in 100 were SMuRF-less. This rate is lower than that reported by most of published studies, mainly due to the high prevalence of the 4 SMuRFs. SMuRF-less patients were younger, had less comorbid disease, received less secondary prevention pharmacotherapy and had higher rate of one year mortality than those with SMuRFs.Clinical Trials: The study is registered with ClinicalTrials.gov, unique identifier number NCT06199869.Keywords: atherosclerotic cardiovascular disease, standard modifiable risk factors, SMuRF-less patients, Middle Eastern patients